A new look at acid catalyzed deacetylation of carbohydrates: A regioselective synthesis and reactivity of 2-O-acetyl aryl glycopyranosides; Carbohydrate Research; Vol. 458-459 - Stepanova E. V. Elena Vladimirovna; Nagornaya M. O. Marina Olegovna; Filimonov V. D. Viktor Dmitrievich; Belyanin M. L. Maksim L'vovich; Valiev R. R. Rashid Rinatovich; Drozdova A. Anna; Cherepanov V. N. Viktor Nikolaevich (2018, 2018)
Title screen